2009
DOI: 10.1186/1471-2458-9-253
|View full text |Cite
|
Sign up to set email alerts
|

"Get off the sofa and go and play": Family and socioeconomic influences on the physical activity of 10–11 year old children

Abstract: Background: Physical activity declines as children approach puberty. Research has focussed on psychosocial, environmental, and demographic determinants. This paper explores how family and socioeconomic factors are related to children's physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 30 publications
11
128
1
7
Order By: Relevance
“…In regard to parents' influence on children's PA, our findings show that those parents who participate in PA with their children was positively associated with children's frequency and duration of PA with a weaker relationship. However, in general meaning when we added the confounding factors, our results show that parents' physical co-activity was negatively related to frequency of children's PA in UGS, which means parents' participation in children's PA negatively affects frequency of children's PA. On the other hand, similarly to previous studies (Sigmund, et al, 2008;Brockman, et al, 2009;Zecevic, et al, 2010), we found that frequency of parents' PA with children was associated with frequency of children's PA and duration of parents' PA with children was associated with duration of children's PA in UGS. One of the possible explanations for the findings is that when parents take their children to parks or playgrounds for PA, they try to guard them due to the various concerns such as fear of traffic accidents, teenage gangs, or fear of strangers (Clements, 2004;Veitch, et al, 2006), parents may tend to limit children's visit to the UGS for PA. Alternatively, parents' responsibilities at home may have negatively affected frequency of children's PA.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In regard to parents' influence on children's PA, our findings show that those parents who participate in PA with their children was positively associated with children's frequency and duration of PA with a weaker relationship. However, in general meaning when we added the confounding factors, our results show that parents' physical co-activity was negatively related to frequency of children's PA in UGS, which means parents' participation in children's PA negatively affects frequency of children's PA. On the other hand, similarly to previous studies (Sigmund, et al, 2008;Brockman, et al, 2009;Zecevic, et al, 2010), we found that frequency of parents' PA with children was associated with frequency of children's PA and duration of parents' PA with children was associated with duration of children's PA in UGS. One of the possible explanations for the findings is that when parents take their children to parks or playgrounds for PA, they try to guard them due to the various concerns such as fear of traffic accidents, teenage gangs, or fear of strangers (Clements, 2004;Veitch, et al, 2006), parents may tend to limit children's visit to the UGS for PA. Alternatively, parents' responsibilities at home may have negatively affected frequency of children's PA.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies show that parents who are generally the primary decision makers for their children's daily schedules may be an important means for encouraging children to be more PA (Sigmund, et al, 2008;Brockman, et al, 2009;Zecevic, et al, 2010). Children who received more parental support for PA, for instance, were found to be 6.3 times more likely to be highly active than inactive (Zecevic, et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Strength of behavioral influence also appears to differ across parent-child dyads (for example, mother-daughter, mother-son, father-daughter, father-son) (Craig et al, 2013;DiLorenzo, Stucky-Ropp, Vander Wal, & Gotham, 1998). Financial constraints among lower SES families may decrease family support for and participation in structured physical activity programs (Brockman et al, 2009). …”
Section: Parent-child Physical Activity Correlatesmentioning
confidence: 99%